Small-scale Fisheries Management Frameworks and Approaches for the Developing World - Pomeroy, Robert S (CABI, 2014)
This book is about small-scale ﬁ sheries (SSF) in the developing world, that is, most of the world’s ﬁ sheries. Globally, about 97% of the people directly involved in ﬁ sheries work in the developing world and they catch about half the total world catch. In the developing world, SSF account for 56% of catch and 91% of people working in ﬁ sheries. Small-scale ﬁ sheries make important but poorly quantiﬁ ed contributions to national and regional economies, to the food security and development of many millions of people and provide an important lever for achieving the Millennium Development Goals, particularly within rural areas. Individually, SSF have a range of attributes that make them and the people that depend upon them vulnerable to threats operating from the largest global scale (e.g. distortions in trade and markets, and climate change) to the smallest internally derived process (e.g. over- ﬁ shing and conﬂ ict). As a generalization, ﬁ shers suffer poorly deﬁ ned rights, are among the poorest and most marginalized parts of society and are poorly represented in national and international policy forums. When viewed from an assessment and management perspective, these attributes are often compounded by sparse data, weak institutions within communities, overﬁ shed stocks, degraded ecosystems and lack of alternative livelihoods. Past failures to address these issues have had signiﬁ cant social consequences and have affected livelihoods, increased vulnerability to poverty and meant less availability of ﬁ sh protein per capita. Historically, development interventions for the ﬁ sheries sector have sought to reduce pov- erty through accelerated economic growth, improvements in technology and infrastructure and market-led economic policy reform. The limited results of these interventions, however, has led to a re-examination of the causes of poverty, the recognition of the signiﬁ cance of vulnerability and the recognition of the need for new strategies for poverty reduction. There is increasing recognition that establishing appropriate pro-poor governance for ﬁ sheries management is cen- tral to maximizing the contribution of ﬁ sheries in poverty alleviation and food security. Pro- poor strategies that include rights-based approaches, co-management regimes and ﬁ shing capacity reduction are essential for increased wealth generation from small-scale ﬁ sheries.